Hacker, hoaxer, whistleblower, spy : the many faces of Anonymous - Coleman, E. Gabriella, 1973- (London ; New York : Verso, 2014)
"Here is the ultimate book on the worldwide movement of hackers, pra nksters, and activists that operates under the non-name Anonymous, by t he writer the Huffington Post says "knows all of Anonymous' deepest, da rkest secrets."Half a dozen years ago, anthropologist Gabriella Coleman set out to study the rise of this global phenomenon just as some of it s members were turning to political protest and dangerous disruption (b efore Anonymous shot to fame as a key player in the battles over WikiLe aks, the Arab Spring, and Occupy Wall Street). She ended up becoming so closely connected to Anonymous that the tricky story of her inside-out side status as Anon confidante, interpreter, and erstwhile mouthpiece f orms one of the themes of this witty and entirely engrossing book.The n arrative brims with details unearthed from within a notoriously mysteri ous subculture, whose semi-legendary tricksters--such as Topiary, tflow , Anachaos, and Sabu--emerge as complex, diverse, politically and cultu rally sophisticated people. Propelled by years of chats and encounters with a multitude of hackers, including imprisoned activist Jeremy Hammo nd and the double agent who helped put him away, Hector Monsegur, Hacke r, Hoaxer, Whistleblower, Spy is filled with insights into the meaning of digital activism and little understood facets of culture in the Inte rnet age, including the history of "trolling," the ethics and metaphysi cs of hacking, and the origins and manifold meanings of "the lulz.""--
"Here is the definitive book on the worldwide movement of hackers, p ranksters, and activists that operates under the name Anonymous, by the woman the Chronicle of Higher Education calls "the leading interpreter of digital insurgency" and the Huffington Post says "knows all of Anon ymous' deepest, darkest secrets." Half a dozen years ago, anthropologis t Gabriella Coleman set out to study the rise of this global collective just as some of its adherents were turning to political protest and di sruption (before Anonymous shot to fame as a key player in the Arab Spr ing and Occupy Wall Street). She ended up becoming so closely connected to Anonymous that some Anons claimed her as "their scholar." Hacker, H oaxer, Whistleblower, Spy brims with detail from inside a mysterious su bculture, including chats with imprisoned hacker Jeremy Hammond and the hacker who helped put him away, Hector "Sabu" Monsegur. It's a beautif ully written book, with fascinating insights into the meaning of digita l activism and little understood facets of culture in the Internet age, such as the histories of "trolling" and "the lulz.""--
Keywords: Anonymous (Group); Hacktivism; Internet -- Political aspects